Aspectos simbólicos da prática da leitura literária em contextos de adversidade - Jéssica Patrícia Silva de Sá (2022)
Reading literary works is an experience that awakens a huge range of sensations, feelings, thoughts and reflections in readers. Therefore, this research aimed to investigate the symbolic appropriation of literary reading by readers in situations of adversity, with regard to physical, psychological or social weaknesses. To achieve the general objective, the following specific objectives were considered: to characterize the symbolic appropriation of literary reading by readers; understand the relationship between reading experiences and coping with adverse situations - be they physical, psychological or social weaknesses. The investigation is linked to the view of Information Science on the processes of symbolic appropriation, bias pertinent to the study of the subjects and the understanding of the ways in which they appropriate information. The theoretical contribution included discussions about reading, literature and the interrelationships between reader and text. The very nature of the object of study evoked the need to use a qualitative approach, effected by the combination of the Clinical Approach to Information and Oral History methods. The semi-structured interview and the critical incident were adopted as data collection techniques, while content analysis was used as a means of data analysis. The intentional sample was composed of five readers belonging to a group of collective reading of an instant messaging application. The analysis of the data resulted in the creation of three major categories, namely: life stories and reading trajectories, symbolic appropriation of literary reading, reading experiences in coping with adverse situations. The analysis showed that reading is not a simple distraction, a mere unpretentious pleasure, but an affective, social and existential experience, capable of providing autonomy, elucidating singular experiences, promoting psychic activity, elaborating emotions and thoughts. The images chosen by the research collaborators were discussed as symbolic representations of their own reading and of themselves as readers, which resulted in the composition of five modes of symbolic appropriation or subcategories of symbols attributed to the practice of reading: emotional balance, escape/refuge, identity, connection, elaboration of the death. It was understood that literary reading in a priori unfavorable contexts acts as a support for important psychic processes: processing/integration, circum-ambulation, identification/catharsis, consolation, amplification. Finally, the research proposed the concept of fluid reading, in which the reader is able to be guided by his current need and move through different reading profiles, in order to meet his psychological, emotional and social needs. Such a profile was evidenced in this investigation, categorizing the reader who appropriates literary texts in a dynamic and intuitive way in order to face adversity.